Development of Board Game Learning Media to Enhance Fifth-Grade Students’ Interest in IPAS at SD Negeri 06 Kampung Lapai - Ilahi, Rahmat; Prananda, Gingga; Ayunis, Ayunis; Oktira, Yona Syaida (The Future of Education Journal, 2025)
The purpose of this study is to determine the validity, practicality, and effectiveness of implementing board game media to increase the learning interest in Science and Social Studies (IPAS) among fifth-grade students at SD Negeri 06 Kampung Lapai. This research employed a qualitative approach with an R&D method based on the ADDIE (Branch) model. Data collection techniques used a questionnaire instrument. The media was designed in the form of a board game measuring 45 × 30 cm. Product validity results consisted of expert validation, namely linguists, material experts, and content experts. Product practicality results consisted of teachers’ responses, while product effectiveness results were obtained from students’ responses. The validation results from the linguist reached 77% (valid category), the material expert 86% (very valid category), and the content expert 90% (very valid category). The practicality results obtained 78% (practical category), and the product effectiveness reached 94% (very interesting category). Based on these findings, the Board Game “Snakes and Ladders” can be used in the IPAS learning process, particularly in the material “What is My Regional Culture Like?”, to foster students’ learning interest. This was evidenced by the questionnaire assessment results of students’ learning interest, which reached 94% (very interesting category). From these results, it can be concluded that the Snakes and Ladders Board Game is highly feasible to be used in the IPAS learning process for the material “What is My Regional Culture Like?” in elementary schools.